Child penalties in Canada - Marie Connolly; Marie Mélanie Fontaine; Catherine Haeck (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Groupe de recherche sur le capital humain (GRCH), 2023)
Having children has a sizeable impact on women's labour outcomes, but not on men's. The differential effects of children by gender are referred to as child penalties, and are now documented in many countries. In this paper, we exploit the Longitudinal and International Study of Adults to estimate Canadian child penalties in both earnings and employment for a period going from five years before the birth of the first child to 10 years after. Using an event study methodology (Kleven et al., 2019a), we find large and persistent negative effects of parenthood for mothers, but not fathers. Mothers' earnings decrease by 49% the year of birth, with a penalty still at 34.3% 10 years after; the corresponding penalty in employment down 14.2%. We also document larger negative impacts of parenthood for women who had multiple children or those with a lower education level. We finally provide suggestive evidence that family policies such as parental leave and subsidized childcare may help reduce child penalties.
Keywords: J13; J31; J38; 330; child penalties; family gap; Canada; family policies; subsidized childcare